Auditory event-related potentials based on name stimuli: A pilot study - Zhao, Jindi; Yang, Yuancheng; An, Xingwei; Liu, Shuang; Du, Hongyin; Ming, Dong (Frontiers in Neuroscience, 2022)
Recent years, diagnostic studies of brain disorders based on auditory event-related potentials (AERP) have become a hot topic. Researches showed that AERP might help to detect patient consciousness, especially using the subjects’ own name (SON). In this study, we conducted a preliminary analysis of the brain response to Chinese name stimuli. Twelve subjects participated in this study. SON were used as target stimuli for each trial. The names used for non-target stimuli were divided into three Chinese character names condition (3CC) and two Chinese characters names condition (2CC). Thus, each subject was required to be in active (silent counting) and passive mode (without counting) with 4 conditions ([passive, active] × [3CC, 2CC]).We analyzed the spatio-temporal features for each conditions, and we used SVM for target vs non-target, classification. The results showed that the passive mode under 3CC conditions showed a similar brain response to the active mode, and when 3CC was used as a non-target stimulus, the brain response induced by the target stimulus would have a better interaction than 2CC. We believe that the passive mode 3CC may be a good paradigm to replace the active mode which might need more attention from subjects. The results of this study can provide certain guidance for the selection and optimization of the paradigm of auditory event-related potentials based on name stimulation.